Nitrogen, Phosphorus, and Potassium Fertilization for Newly Established Tall Fescue - D. W. Sweeney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
First-year production of tall fescue (Site 1 in 2013 and Site 2 in 2014) was affected by nitrogen (N) and phosphorus (P) but not potassium (K) fertilization. Environmental conditions likely influenced the growth of the fescue and the response to fertilizer N and P in the first year of production at the two sites.
Keywords: nitrogen; phosphorus; potassium; fertilization; fescue